Preparation and Properties of 2D Materials - Cho, Byungjin; Kim, Yonghun (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Since the great success of graphene, atomically thin-layered nanomaterials, called two dimensional (2D) materials, have attracted tremendous attention due to their extraordinary physical properties. Specifically, van der Waals heterostructured architectures based on a few 2D materials, named atomic-scale Lego, have been proposed as unprecedented platforms for the implementation of versatile devices with a completely novel function or extremely high-performance, shifting the research paradigm in materials science and engineering. Thus, diverse 2D materials beyond existing bulk materials have been widely studied for promising electronic, optoelectronic, mechanical, and thermoelectric applications. Especially, this Special Issue included the recent advances in the unique preparation methods such as exfoliation-based synthesis and vacuum-based deposition of diverse 2D materials and also their device applications based on interesting physical properties. Specifically, this Editorial consists of the following two parts: Preparation methods of 2D materials and Properties of 2D materials